Budaya Rimpu sebagai Eksistensi Perempuan Islam di Tanah Bima - Ayu Fitriana; Suharno Suharno (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
Bima people are known to be very religious, one of them being the Bima women who always cover their genitals. One of the well-known covers of genitalia in Bima is to use a Sarong, called the Rimpu. The purpose of this study wants to know the Rimpu culture as the existence of Islamic women in the land of Bima. This article compiled using the library research method. The results provided are Rimpu is genital cover clothes made of Sarong. The Rimpu has been in Bima since the first time Islam entered and applied to the sultanate in the land of Bima. The Rimpu divided into two types, namely regular Rimpu and Mpida Rimpu. The usual Rimpu split into two, namely Rimpu Colo and Rimpu Cili. The Rimpu Mpida divided into three kinds of Rimpu, namely, Rimpu Mpida, Rimpu Gala And Rimpu Cili. The Rimpu has multiple functions in addressing the times, as a religious identity, distinctive characteristics of Bima culture, and protector of women in interacting with the opposite sex. Nowadays, the government is trying to preserve it by holding a cultural parade every year.